Interleukin-4 and interleukin-13 enhance CCL26 production in a human keratinocyte cell line, HaCaT cells - Kagami, S (Blackwell Science Inc, 2005)
Eotaxin-2/CCL24 and eotaxin-3/CCL26 are CC chemokines and their receptor, CC chemokine receptor 3 is preferentially expressed on eosinophils. It was reported that vascular endothelial cells and dermal fibroblasts produced CCL26. However, the regulation of CCL24 and CCL26 production in keratinocytes has not been well documented. We investigated the expression and production of CCL24 and CCL26 in the human keratinocyte cell line, HaCaT cells. Reverse transcription and polymerase chain reaction was performed using these cells and Enzyme-linked immunosorbent assay was carried out using supernatant of these cells. The production of CCL24 in HaCaT cells was slightly enhanced by IL-4 and that of CCL26 was strongly enhanced by IL-4 and IL-13. Furthermore, TNF-α generated a synergistic effect on IL-4 enhanced CCL26 production. Dexamethasone, IFN-γ and the p38 mitogen-activated protein kinase inhibitor SB202190 inhibited IL-4 enhanced CCL26 production. IL-4 enhanced production of CCL26 was inhibited by leflunomide and JAK inhibitor 1, but not by JAK3 inhibitor, which indicates that it is mediated by JAK1-STAT6-dependent pathway. This result also strongly suggests the involvement of the type 2 IL-4 receptor in IL-4 enhanced production of CCL26. These results suggest that keratinocytes are involved in the migration of CC chemokine receptor 3 positive cells such as eosinophils in a Th2-dominant situation like atopic dermatitis.